Iranian household values and perception with respect to housing attributes - Moghimi, V. (Elsevier Ltd, 2016)
Designing houses matching user's values is essential for delivering quality housing. However, designer-user gap and difficulties in identifying Iranian household values have resulted in developing inappropriate houses. Therefore, this study has been set to investigate user perceptions of value creators in dwelling space design and to clarify user's perceptual orientation toward housing attributes. Data were gathered from the occupants of mass-produced apartments built in Bushehr, Iran through two sequential complementary stages. Examining 15 occupants using MEC model and soft laddering were followed by distributing 150 hard laddering questionnaire surveys. Based on our findings, value creators encompass psychological and functional aspects. Value creators included provision of beautiful environment. Furthermore, designing efficient building which also provides adequate space was vital. Providing occupant comfort and privacy and at the same time enhancing their intimacy and integrity were also seen as crucial. The desired aspects of housing environment also involved a pleasant environment which improves human vitality. Providing designers with occupants' mental process and perception results in enhancing the appropriateness of dwelling space design.